2020
DOI: 10.14233/ajchem.2020.22696
|View full text |Cite
|
Sign up to set email alerts
|

Annonaine an Alkaloid from the Leaves of Custard Apple (Annona squamosa): A Comprehensive Review on its Phytochemicals and Pharmacological Activities

Abstract: Annona squamosa is most widely distributed in tropical and subtropical region native to tropical America comes under the Annonaceae family. It is a widely used tree having edible fruits called as custard apple which is eatable. Annona squamosa plant also contains 35-42 mg/100 g of vitamin C and significant value of nutrient like thiamine, amino acid, riboflavin, niacin, calcium, potassium and dietary fibers. It also contains the phytoconstituents like diterpenes, alkaloids, cyclopeptides and annonaceous acetog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…40 Dash et al proposed in the literature that the secondary metabolites like flavonoids, phenols, alkaloids, tannins, steroids, etc., present in the plants are responsible for showing beneficial effects including antimicrobial properties. 5 Terpenes are the chief essential components of the plant extract that showed good antimicrobial activity. 41 Yamunadevi et al suggested that tannins, and steroids are responsible to have antidiarrheal activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…40 Dash et al proposed in the literature that the secondary metabolites like flavonoids, phenols, alkaloids, tannins, steroids, etc., present in the plants are responsible for showing beneficial effects including antimicrobial properties. 5 Terpenes are the chief essential components of the plant extract that showed good antimicrobial activity. 41 Yamunadevi et al suggested that tannins, and steroids are responsible to have antidiarrheal activity.…”
Section: Resultsmentioning
confidence: 99%
“…4 Annona squamosa Linn is a shrub that belongs to the family Annonaceae. 5 It is a perennial tree with thin, oblong-lanceolate, alternate leaves. It is abundantly native to tropical America, the Caribbean, and Indomalaya.…”
mentioning
confidence: 99%
See 2 more Smart Citations